Optimal Timing of Diffusion-Weighted Imaging to Avoid False-Negative Findings in Patients With Transient Ischemic Attack. Issue 7 (July 2017) - Shono, Kenji; Satomi, Junichiro; Tada, Yoshiteru; Kanematsu, Yasuhisa; Yamamoto, Nobuaki; Izumi, Yuishin; Kaji, Ryuji; Harada, Masafumi; Nagahiro, Shinji
Abstract : Background and Purpose—: We aimed to investigate the optimal timing of diffusion-weighted imaging (DWI) in patients with transient ischemic attack (TIA). Methods—: Seventy-three consecutive patients with TIA underwent DWI on admission (initial DWI) and at 24 hours after admission (second DWI). Patients were divided into 2 groups based on initial DWI findings in relation to the second examination: false negative (group 1) and other (group 2). The probability of initial false-negative findings was determined for each hour from TIA onset to initial DWI. Multivariate analysis was used to evaluate the independent risk factors associated with false-negative findings on initial DWI. Results—: Of the 73 patients examined (56 men; mean age, 68 years), 9 (12%) were categorized into group 1. The latency from TIA onset to initial DWI was 1.7±0.6 hours for group 1 (range, 1–2.8 hours) and 3.3±2.6 hours for group 2 (range, 35 minutes to 12 hours). The probability of false-negative findings on initial DWI decreased in a time-dependent manner (25%, 21%, and 7% for 1, 2, and 3 hours, respectively), and no false-negative findings were observed on initial DWI performed at >3 hours from symptom onset. Short latency (⩽2 hours) from TIA onset to initial DWI was an independent risk factor related to false-negative findings (odds ratio, 13.11; 95% confidence interval, 1.07–161.38; P =0.045). Conclusions—: If the duration between TIA symptom onset and initial DWI is <2 hours, a repeat examination should be performed to minimize the risk of false-positive findings. Abstract : Supplemental Digital Content is available in the text.